Duo out for camp - Syahrina, Ahmad (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
26 - 28 March 2010. What could possibly happen when groups of students went out for camping. A hullabaloo of aesthetic and energetic group of students, you can bet! This year, an enthralling and enjoyable camping event for Arabic and Japanese students, was held by the Department of Foreign Languages, Centre for Modern Languages & Human Sciences, UMP at Dusun Eco Resort, Bentong, Pahang.